A study exploring the relationship between ethnic identity and school connectedness in adolescents - Chung, Kirsten C. Y. (2019)
This study advances our understanding on the relationship between ethnic identity and school connectedness in adolescents. Exploration in this research area is fundamental as the UK has shown an increased prevalence for which wellbeing difficulties can be identified, and an increase in ethnic diversity in children and young people (NHS Digital, 2018 and Ainscow et al., 2016). The associated challenges for education provisions are that wellbeing requires more action towards promotion and intervention, and ethnic group differences should be minimised to encourage equality. Applied to an educational setting, research has shown that both school connectedness and ethnic identity can contribute to the prediction of an individual’s outcomes, e.g. academic attainment, however, it appears from the results of the study’s systematic literature review that little research in the UK has examined the relationship between the two.